The Distinct Role of Medium Spiny Neurons and Cholinergic Interneurons in the D(2)/A(2A) Receptor Interaction in the Striatum: Implications for Parkinson's Disease - Tozzi, Alessandro (J Neurosci, 2011)
A(2A) adenosine receptor antagonists are currently under investigation as potential therapeutic agents for Parkinson's disease (PD). However, the molecular mechanisms underlying this therapeutic effect is still unclear. A functional antagonism exists between A(2A) adenosine and D(2) dopamine (DA) receptors that are coexpressed in striatal medium spiny neurons (MSNs) of the indirect pathway. Since this interaction could also occur in other neuronal subtypes, we have analyzed the pharmacological modulation of this relationship in murine MSNs of the direct and indirect pathways as well in striatal cholinergic interneurons. Under physiological conditions, endogenous cannabinoids (eCBs) play a major role in the inhibitory effect on striatal glutamatergic transmission exerted by the concomitant activation of D(2) DA receptors and blockade of A(2A) receptors in both D(2)- and D(1)-expressing striatal MSNs. In experimental models of PD, the inhibition of striatal glutamatergic activity exerted by D(2) receptor activation did not require the concomitant inhibition of A(2A) receptors, while it was still dependent on the activation of CB(1) receptors in both D(2)- and D(1)-expressing MSNs. Interestingly, the antagonism of M1 muscarinic receptors blocked the effects of D(2)/A(2A) receptor modulation on MSNs. Moreover, in cholinergic interneurons we found coexpression of D(2) and A(2A) receptors and a reduction of the firing frequency exerted by the same pharmacological agents that reduced excitatory transmission in MSNs. This evidence supports the hypothesis that striatal cholinergic interneurons, projecting to virtually all MSN subtypes, are involved in the D(2)/A(2A) and endocannabinoid-mediated effects observed on both subpopulations of MSNs in physiological conditions and in experimental PD.